Hydrogel armed with Bmp2 mRNA-enriched exosomes enhances bone regeneration - Zhujun Yang; Xuejian Li; Xueqi Gan; Mengying Wei; Chunbao Wang; Guodong Yang; Yimin Zhao; Zhuoli Zhu; Zhongshan Wang (2023)
Sustained release of bioactive BMP2 (bone morphogenetic protein-2) is important for bone regeneration, while the intrinsic short half-life of BMP2 at protein level cannot meet the clinical need. In this study, we aimed to design Bmp2 mRNA-enriched engineered exosomes, which were then loaded into specific hydrogel to achieve sustained release for more efficient and safe bone regeneration.Bmp2 mRNA was enriched into exosomes by selective inhibition of translation in donor cells, in which NoBody (non-annotated P-body dissociating polypeptide, a protein that inhibits mRNA translation) and modified engineered BMP2 plasmids were co-transfected. The derived exosomes were named ExoBMP2+NoBody. In vitro experiments confirmed that ExoBMP2+NoBody had higher abundance of Bmp2 mRNA and thus stronger osteogenic induction capacity. When loaded into GelMA hydrogel via ally-L-glycine modified CP05 linker, the exosomes could be slowly released and thus ensure prolonged effect of BMP2 when endocytosed by the recipient cells. In the in vivo calvarial defect model, ExoBMP2+NoBody-loaded GelMA displayed great capacity in promoting bone regeneration.Together, the proposed ExoBMP2+NoBody-loaded GelMA can provide an efficient and innovative strategy for bone regeneration.